PREPARATION AND CHARACTERIZATION OF MICROWAVE-ASSISTED CHLORINATED GLUCOSE USING PALM FATTY ACID DISTILLATE FOR BIODIESEL PRODUCTION - Zaki Yamani Zakaria; Muhamad Hariz Adam Hussin Khan; Norzita Ngadi; Mazura Jusoh (PERINTIS eJournal, 2021)
The development of heterogeneous acid catalyst has gained a broader attention over the last decade. This is due to the incredible solutions to several problems in biodiesel industry including the separation treatment after process, avoid saponification problems and capable to directly esterify low quality feedstock with high content of free fatty acid (FFA). This study was focusing on the development of the chlorinated glucose acid catalyst (CGAC) prepared via microwave assisted method for esterification of palm fatty acid distillate (PFAD) to biodiesel. Preparation of the catalyst was done by varying its power levels (high 800W), medium high 560W, medium low 240W and low 80W). Characterizations of the catalyst were carried out by using Brunauer Emmet and Teller (BET), Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD), Temperature-Programmed Desorption – Ammonia (TPD-NH3) and Fourier Transform Infrared (FTIR). For catalytic testing of the catalysts prepared, molar ratio of methanol to PFAD was 10:1, 2.5 wt% of catalysts loading, reaction time at 90 minutes as well as reaction temperature at 70°C were fixed to produce the biodiesel at the same standard. From the Gas Chromatography – Flame Ionization Detector (GC-FID) result, CGAC prepared with medium high power levels showed the highest percentage yield which was up to 90.21%. In addition, the reaction kinetics of biodiesel production for medium high power levels CGAC had been developed. The optimum condition obtained was at 70°C with the rate of reaction of 0.0241 mol dm-3 s-1 and activation energy of esterification process is 40.471 kJ/mol.K